Disruptive Knowledge in Education for Reconciliation: The Effects of Indigenous Course Requirements on Non-Indigenous Students’ Attitudes - Siemens, Jeremy; Neufeld, Katelin H. S. (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
Following the Truth and Reconciliation Commission of Canada, various institutions have embarked on diverse educational initiatives in the name of creating equitable and respectful relationships between Indigenous and non-Indigenous Peoples. One such initiative is the University of Winnipeg’s mandate that all undergraduate students fulfill an Indigenous Course Requirement (ICR). Using the framework of disruptive knowledge, this mixed-methods study investigated the impact of select ICR courses on non-Indigenous students’ attitudes. Results revealed increased recognition of discriminations facing Indigenous Peoples, increased support for systemic change, and self-described behavioural changes. At the same time, these results highlight the limitations of such courses within a settler-colonial context.